Using affective reading strategies in teaching german language as a foreign language at a primary school level - Marija B. Nijemčević Perović (University of Belgrade, Teacher Education Faculty, 2021)
The aim of the research was to determine the level of frequency of using affective reading strategies in teaching German as a foreign language at a primary school level. The tasks referred to examining the contribution of biological (gender and age) and external factors (assessment of reading activities in German) to the level of frequency of their use. The level of frequency of application of affective strategies as a dependent variable was measured against these independent variables. The descriptive method was used for processing and interpretation of the results, while the correlation method is used in the part of the paper in which we deal with the relationship between predictor variables and the cumulative score on the scale. At the same time, the research was supposed to show the extent to which an implicit strategic input as an independent variable contributes to the frequency of using the examined strategies. In this part, the method of an experiment with one group was used. The data collection technique was a survey, and its instrument was a questionnaire. The results show a low frequency of using affective strategies, which is more pronounced in female than in male pupils. With age, the examined phenomenon becomes less pronounced, while pupils with a higher achievement and better language competencies more often use affective strategies to manage their attitudes and emotions. After exposing the respondents to the strategic input, the statistically significant differences caused by exposing the pupils to an implicit teaching of affective strategies were determined by repeated measurements.